Teaching and learning methodologies in teaching Sciences at Euclides Moreira Pontes School located in the Quilombola Community São Benedito do Vizeu-Pará - Manoel Leão Lopes Júnior; Erica Fernandes Cantão; Eder Jacson Dias Pereira; Luely Oliveira da Silva; Lourivaldo da Silva Santos; Railda Neyva Moreira Araújo; Marivaldo José Costa Corrêa; Gabriel Dante da Silva Monteiro (Universidade Federal do Norte do Tocantins, 2022)
This work deals with teaching and learning methodologies aimed at the science class at the Euclides Moreira Pontes School located in the Quilombola são Benedito do Vizeu community. The research discusses the fragmentation of teaching and learning in the area of sciences that are worked in a traditional way, thus proposing methodological proposals aimed at improving learning. Its objective is to propose methodologies in science education, focused on educational aspects, with educational practices that strengthen the historical singularity of the studied quilombola territory. For data collection, interviews were carried out following an application script, directed to students and a teacher of the science discipline, using observation in science classes, participation and development of new teaching methodologies such as: experiments, practical classes, research, games, in order to improve the teaching-learning process. At the end of this work it was possible to observe that the lack of differentiation of methodological practices in science classes, contributes to the lack of motivation, interest and enthusiasm of the students, harming the whole process of teaching and learning.